2016
DOI: 10.1002/hbm.23443
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for superior neurobiological and behavioral inhibitory control abilities in non-offending as compared to offending pedophiles

Abstract: Neurobehavioral models of pedophilia and child sexual offending suggest a pattern of temporal and in particular prefrontal disturbances leading to inappropriate behavioral control and subsequently an increased propensity to sexually offend against children. However, clear empirical evidence for such mechanisms is still missing. Using a go/nogo paradigm in combination with functional magnetic resonance imaging (fMRI) we compared behavioral performance and neural response patterns among three groups of men match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 56 publications
1
41
0
2
Order By: Relevance
“…Supporting functional magnetic resonance imaging (fMRI) and EEG studies (see below), neuropsychological research has shown executive dysfunctions in child sexual offenders (92). Interestingly, a recent neuropsychological study supports the results by Kärgel et al (91) in so far as executive dysfunctions (worsened response inhibition abilities) are related to offense status rather than pedophilic preference (93).…”
Section: Functional Imaging-functional Magnetic Resonance Imagingmentioning
confidence: 57%
See 3 more Smart Citations
“…Supporting functional magnetic resonance imaging (fMRI) and EEG studies (see below), neuropsychological research has shown executive dysfunctions in child sexual offenders (92). Interestingly, a recent neuropsychological study supports the results by Kärgel et al (91) in so far as executive dysfunctions (worsened response inhibition abilities) are related to offense status rather than pedophilic preference (93).…”
Section: Functional Imaging-functional Magnetic Resonance Imagingmentioning
confidence: 57%
“…Furthermore, an increased inhibition related activity in left posterior cingulate and left superior frontal cortex, areas associated with effective cognitive functioning, was found in non-offending pedophiles. According to Kärgel et al, these data indicate a better inhibitory control in pedophiles who successfully avoid committing handson sexual offenses against children (91).…”
Section: Functional Imaging-functional Magnetic Resonance Imagingmentioning
confidence: 96%
See 2 more Smart Citations
“…Lastly, all of our patients had a history of sexual offending against children. According to previous research, SOC with PD present reduced inhibitory control compared to men with PD but no offence history (Kärgel et al, 2016;Massau et al, 2017). Thus, impaired inhibitory control might increase the risk of offending, and different levels of impairment might be associated with contact compared to noncontact or no offending.…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 92%